Evaluation of Commercial Banks' Shares in Damascus Stock Exchange using Residual Income Model /RIM/ (Journal of Hama University, 2019)
This research aimed to determine the ability of Residual Income Model to evaluate the of commercial banks listed on Damascus stock exchange, during the period from 1/1/2014 to 31/12/2016. To achieve this purpose, intrinsic value was calculated for bank BEMO and International Bank for Trade & Financing using required rate of return (CAPM) to get discounted current value for residual income and added it to book value and compare it with market price of share, then conduct statistical analysis using a spss program. Many of results have been reached, the most important of which are; the absence of significant statistical differences between the real values of the shares and their prices in the market , shares' prices   in Damascus Stock Exchange are also very low  and their returns were negative, which led to a decrease in the required return on the stock ,consequently, the effectiveness of the residual income model didn’t appear in the stock valuation because prices  did not fully reflect stocks value due to factors other than profits such as the economic and political conditions of the country.